Leaching and uptake of nitrogen and phosphorus from cow slurry and fox manure in a lysimeter trial - Kemppainen, Erkki (Agricultural Research Centre of Finland, 1995)
Lysimetrikokeessa tutkittiin maalajin, levitysajan sekä nitrifikaatioinhibiittorin (Didin) vaikutusta naudan lietelannan ja ketun lannan typen ja fosforin huuhtoutumiseen ja hyväksikäyttöön. Valunta ja kokonaistypen huuhtoutuminen turvemaasta olivat noin kaksinkertaisia hietaan verrattuna. Nitraattitypen huuhtoutumisessa ei ollut merkittävää eroa, mutta ammoniumtyppeä turvemaasta huuhtoutui 50-kertainen määrä ja orgaanista typpeä 3-kertainen määrä hietaan verrattuna. Turvemaasta huuhtoutui myös kokonaisfosforia 23-kertainen määrä ja Tiukoista fosforia 39-kertainen määrä hietaan verrattuna. Naudan lietelannasta ja ketun lannasta huuhtoutui suunnilleen yhtä paljon typpeä. Typpeä huuhtoutui vähiten toukokuussa levitetystä lannasta. Didin ei vähentänyt typen huuhtoutumista merkitsevästi. Ketun lannasta huuhtoutui turvemaalla selvästi enemmän fosforia kuin naudan lietelannasta. Lannan levitysaika ei vaikuttanut fosforin huuhtoutumiseen. Turvemaa tuotti huomattavasti suurempia ohrasatoja kuin hieta. Ketun lanta oli selvästi naudan lietelantaa tehokkaampaa lannoitetta. Ensimmäisenä koevuonna lannan levitys joulukuussa vähensi merkitsevästi sen lannoitusvaikutusta muihin levitysaikoihin verrattuna. Ohran jyvä- ja olkisadon perusteella laskettuna lannan kokonaistypen näennäinen hyväksikäyttö oli 24-41 % ja lannan fosforin hyväksikäyttö 6-51 %. Lannan kokonaistypestä huuhtoutui 4-21 % ja fosforista 0-2,6 %.

The effects of soil type, spreading time and use of a nitrification inhibitor (Didin) on the leaching and uptake of nitrogen and phosphorus from cow slurry and fox manure were studied in a lysimeter trial during 1989-1992. The runoff volume and leaching of total nitrogen in peat soil were double those in fine sand soil. There was no essential difference in the leaching of nitrate nitrogen, but the amount of ammonium nitrogen leached from peat soil was 50-fold and that of organic nitrogen about 3-fold the amounts leached from fine sand soil. The amount of total phosphorus leached from peat soil was 23-fold and that of soluble phosphorus 39-fold the amounts leached from fine sand soil. There were only minor differences between cow slurry and fox manure in the leaching of nitrogen. The least nitrogen was leached after manure application in May. Didin did not have any significant effect. In peat soil, significantly more phosphorus leached from fox manure than from cow slurry. Spreading time had no effect on phosphorus leaching. Considerably higher barley grain yields were harvested from peat soil than from fine sand soil. Fox manure proved to be a much more effective fertilizer than cow slurry. In the first experimental year, December spreading resulted in a lower yield than other spreading times. Of the total nitrogen applied in manure, 24-41 % was recovered in barley yield (grain+straw) and 4-21 % in runoff; the figures for phosphorus were 6-51 % and 0-2.6%, respectively.
Keywords: Ka; karjanlanta; typpi; fosfori; ravinteiden huuhtoutuminen; peat soil; fine and soil; spreading time; nitrification; nitrification inhibitor; nitrate; ammonium; organic nitrogen; soluble phosphorus; runoff